Comparison of dynamic parameters of landing from different heights of professional elite volleyball players - Shokrian, F.; Khezri, D.; Matinhomaee, H.; Fatahi, A. (Journal of Advanced Sport Technology, 2022)
This study aims to compare the dynamic parameters of professional elite volleyball players when landing from different heights. 15 volleyball players selected based on availability participated in the study. The studied skill for different height was set to a percentage of the maximum jump elevation (100% - 75% - 50%). A repeated measures ANOVA model was used to determine the measurements variance differences using SPSS software version 24. The results showed that landing from higher height increased the angular velocity of the rotational axis of the foot while the peak of angular acceleration was lower at the highest elevation. The linear velocity peak also showed lower values at the highest elevation, while the linear acceleration increased with increasing landing elevation. Despite the insignificant effect of different height on the vertical ground reaction force (vGRF) factor, the peak of ankle joint torque in the anterior-posterior axis increased with increasing elevation. Similarly, the maximum ankle angle in the anterior-posterior axis was higher at high elevation than at low elevation. The results showed that volleyball players try to improve the absorption of energy by increasing the range of motion of the ankle joint in the anterior-posterior axis at high elevation.